HCISPP Study Guide. - Virtue, Timothy (Elsevier Science, 2014)
The HCISPP certification is a globally-recognized, vendor-neutral exam for healthcare information security and privacy professionals, created and administered by ISC². The new HCISPP certification, focused on health care information security and privacy, is similar to the CISSP, but has only six domains and is narrowly targeted to the special demands of health care information security. Tim Virtue and Justin Rainey have created the HCISPP Study Guide to walk you through all the material covered in the exam's Common Body of Knowledge. The six domains are covered completely and as concisely as possible with an eye to acing the exam. Each of the six domains has its own chapter that includes material to aid the test-taker in passing the exam, as well as a chapter devoted entirely to test-taking skills, sample exam questions, and everything you need to schedule a test and get certified. Put yourself on the forefront of health care information privacy and security with the HCISPP Study Guide and this valuable certification. Provides the most complete and effective study guide to prepare you for passing the HCISPP exam - contains only what you need to pass the test, and no fluff! Completely aligned with the six Common Body of Knowledge domains on the exam, walking you step by step through understanding each domain and successfully answering the exam questions. Optimize your study guide with this straightforward approach - understand the key objectives and the way test questions are structured.